Implementation of Good Governance and Strategy for the Development of Religious Tourism of Prince Benowo's Cemetery in Improving the Economy of the People - Akbar, Ilma Fathan; Erwin, Erwin; Hidayatullah, Ahmad (Institut Agama Islam Negeri Parepare, 2022)
research was written aim for knowing implementation good governance and strategy development tour religious tomb Pangeran Benowo so that it can unraveled about information related implementation good governance strategy development tour religious tomb Pangeran Benowo. Inner problem research this was how implementation good governance and strategy development which is conducted management and development tour religious Pangeran Benowo tomb. Method used in this research was method approach qualitative because component qualitative covers observation,interview,and research literature. Results of this research show that necessary implementation good governance and build fasilities needed for developing of tour religious tomb Pangeran Benowo that is accessibility,shopping center,place to stay,and tour guide.